Influences on the implementation of community urban agriculture: insights from agricultural professionals - Tiraieyari, Neda; Karami, Roya; Ricard, Robert M.; Badsar, Mohammad (MDPI, 2019)
Limited studies have investigated the relative influence of both external and internal factors in the implementation of community-based urban agriculture (UA) (ICUA). Furthermore, little research exists explaining how different mechanisms might influence urban residents’ decision to participate in UA. Our research tested the direct effect of several predictors on ICUA using structural equational modelling. In addition, we tested the mediation effect between the predictors and the ICUA that may exist as well. Results are based on data from 200 agricultural professionals in the Zanjan province in northwest Iran. We found that “personal characteristics”, “UA positive and negative consequences”, “sociocultural”, and “economic” factors affect ICUA. Among all factors, “personal characteristics” had the strongest direct effect on ICUA. The indirect model incorporating “attitude” provided support for the mediation model. We found “personal characteristics”, “UA positive and negative consequences”, and “sociocultural” influenced ICUA indirectly through “attitude.” Among all factors, “sociocultural” had the strongest indirect effect on ICUA. This information is of use to policy-makers and program planners in identifying points of policy interventions and mechanisms for promoting UA.